RECONSTRUCTING THE BIOLOGICAL CHARACTERISTICS OF PAST PHILIPPINE HUMAN POPULATIONS - Medrana, Jack G.L. (Hukay; Vol 2 No 2, 2014)
Archaeological investigations employing the methods of physical anthropology and the biological sciences have been done on Philippine human remains found in archaeological sites to reconstruct a working biological picture of past populations. These were characterized mostly as to the number of individuals in the site, age at death, stature, bodily deformities, cultural practice and anatomic affinity to other populations. Although almost all individual specimens revealed interesting morphological features while appearing to fall within the type referred to as Mongoloid, a generalization of past Philippine populations is still premature, considering the fact that there is a need for more of these kinds of investigation to expand the database.